Supply's strategic contribution: An empirical reality. Issue 2 (March 2017) - Tchokogué, André; Nollet, Jean; Robineau, Julien
Abstract: Since the mid-1970s, authors from academia and from business have recognized that the strategic contribution made by supply is multi-faceted, although their work does not distinguish among the levels of strategic contribution. This study makes this differentiation by using a systematic literature review of the last 30 years and by performing a content analysis of 131 selected articles. The analysis of the increasing sophistication of supply's strategic contributions leads to three main observations: 1) the different types of contributions can indeed be classified into categories: category I ( support to corporate improvement targets ), category II ( support to the organizational competitive advantage ), and category III ( source of sustainable competitive advantage ); 2) contribution types in category I have been recognized since at least the early 1980s, while recognition has progressively taken place mostly in the 1990s for categories II and III; and 3) the contribution types in category I are perceived both as contributions that the supply function must master before it can take on those in categories II and III, and as contributions expected even when the supply function already contributes well to categories II and III. Therefore, supply professionals should develop their ability to better utilize the currently acknowledged strategic contributions, while being ready to take advantage of the new types of contributions. Highlights: Based on the content analysis of 131 articles (including 74% of an empirical nature). Evidence of the increasing sophistication of supply's strategic contribution over time. The different types of contributions can be classified into three categories. Recognition of the contribution types in categories II and III mostly in the 1990s. Category I contributions must be mastered first.